Young people's experiences of managing Type 1 diabetes at university: a national study of UK university students. Issue 8 (5th July 2018) - Kellett, J.; Sampson, M.; Swords, F.; Murphy, H. R.; Clark, A.; Howe, A.; Price, C.; Datta, V.; Myint, K. S.
Abstract: Aim: Little is known about the challenges of transitioning from school to university for young people with Type 1 diabetes. In a national survey, we investigated the impact of entering and attending university on diabetes self‐care in students with Type 1 diabetes in all UK universities. Methods: Some 1865 current UK university students aged 18–24 years with Type 1 diabetes, were invited to complete a structured questionnaire. The association between demographic variables and diabetes variables was assessed using logistic regression models. Results: In total, 584 (31%) students from 64 hospitals and 37 university medical practices completed the questionnaire. Some 62% had maintained routine diabetes care with their home team, whereas 32% moved to the university provider. Since starting university, 63% reported harder diabetes management and 44% reported higher HbA1c levels than before university. At university, 52% had frequent hypoglycaemia, 9.6% reported one or more episodes of severe hypoglycaemia and 26% experienced diabetes‐related hospital admissions. Female students and those who changed healthcare provider were approximately twice as likely to report poor glycaemic control, emergency hospital admissions and frequent hypoglycaemia. Females were more likely than males to report stress [odds ratio (OR) 4.78, 95% confidence interval (CI) 3.19–7.16], illness (OR 3.48, 95% CI 2.06–5.87) and weight management issues (OR 3.19, 95% CI 1.99–5.11) as barriers to self‐care. Despite these difficulties, 91% of respondents never or rarely contacted university support services about their diabetes. Conclusion: The study quantifies the high level of risk experienced by students with Type 1 diabetes during the transition to university, in particular, female students and those moving to a new university healthcare provider. What's new?: This national survey is unique and captured data from approximately one‐third of all students with Type 1 diabetes at UK universities. Current diabetes care systems for university students are not functioning well, resulting in poor glycaemic control (25% higher HbA1c, 63% increased difficulty in diabetes management), diabetes complications that interrupt studies (43% frequent hypoglycaemia) and excess hospital admissions (25%). Higher risk groups were female students (hypoglycaemia, depression, etc.) and those who had moved healthcare providers (higher HbA1c, hypoglycaemia, ketoacidosis and hospital admissions). Despite these challenges, 91% never/rarely contacted university support services. There is scope for a national approach to improving the focus care pathway.